Archiving and collecting Arctic datasets: Open Arctic Research Index - Abu-Alam, Tamer; Nilsen, Karl Magnus; Odu, Obiajulu; Høydalsvik, Stein (2019)
Poster presentation at the Open Repositories 2019 conference, Hamburg, 10.06.19 - 13.06.19. http://archiv.gwin.gwiss.uni-hamburg.de/or2019/. The number of digital repositories containing publications and datasets on the Arctic region are increasing enormously. Users want relevant information according to their query with minimum interval of time. Scholars are compelled to search the individual repositories to get their desired documents. Open Arctic Research Index (Open ARI), a planned service at UiT - The Arctic University of Norway, aims to collect and index all the openly available Arctic-related publications and datasets in a single open access metadata index. By providing a simple search dialog box to the index, users can search all these repositories and archives in a single operation. The project investigates how such a service can support researchers in their research by making results from Arctic research more visible and better retrievable based on a standardized, interdisciplinary metadata set. The project started by clarifying the need for a new technical solution to collect all the published material using algorithms that allow the best way of filtering relevant records. We have defined 115 possible national and international collaborators who can feed the Open ARI with content. The team will analyze the success opportunities and the challenges in order of planning a full-scale management model.